Investment risks in the contemporary economy - Gutkevych, Svitlana (My University, 2013)
Capital investment for the investor is connected to the extreme risk. Risk is an influencing factor on the investment attractiveness of the industries of economy. Капітальні інвестиції для інвестора пов’язані з граничним ризиком. Ризик є фактором, який впливає на інвестиційну привабливість галузей економіки.
Keywords: risk; investment; profits; investment attractiveness; management; ризик; інвестування; прибутки; інвестиційна привабливість; управління; кафедра міжнародної економіки